Sosialisasi Model Pembelajaran bagi Masyarakat di Kecamatan Umalulu untuk Meningkatkan Kemampuan Literasi dan Numerasi Siswa SD - Erwin Randjawali; Yulita Milla Pakereng; Mayun Erawati Nggaba; Iona Lisa Ndakularak; Stevvileny Angu Bima; Dominggus Bandi; Usman Pati Benau (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
This PkM activity aims to disseminate the results of research that has been carried out by Unkriswina Sumba together with Balitbangda of East Sumba Regency regarding appropriate learning models to improve literacy and numeracy skills of elementary school students in East Sumba Regency. This outreach activity was carried out using lecture and discussion methods. The results of this PkM activity are that research results can be properly disseminated in the form of socialization of learning models, lesson plans, learning modules, and LKPD which are the outputs of Unkriswina Sumba research and Balitbangda East Sumba Regency. Through this PkM activity, it has increased the knowledge of the community in Umalulu District regarding their respective roles in improving the literacy and numeracy skills of elementary school students in the sub-district.